Conformational Dynamics from Ambiguous Zinc Coordination in the RanBP2-Type Zinc Finger of RBM5. Issue 14 (26th June 2020) - Soni, Komal; Martínez-Lumbreras, Santiago; Sattler, Michael
Abstract: The multi-domain RNA binding protein RBM5 is a molecular signature of metastasis. RBM5 regulates alternative splicing of apoptotic genes including the cell death receptor Fas and the initiator Caspase-2. The RBM5 RanBP2-type zinc finger (Zf1) is known to specifically recognize single-stranded RNAs with high affinity. Here, we study the structure and conformational dynamics of the Zf1 zinc finger of human RBM5 using NMR. We show that the presence of a non-canonical cysteine in Zf1 kinetically destabilizes the protein. Metal-exchange kinetics show that mutation of the cysteine establishes high-affinity coordination of the zinc. Our data indicate that selection of such a structurally destabilizing mutation during the course of evolution could present an opportunity for functional adaptation of the protein. Graphical abstract: Unlabelled Image Highlights: RBM5 Zf1 shows conformational exchange conferred by a non-canonical cysteine. Competition between two neighboring cysteines yields dynamic zinc ion coordination. Mutation of the non-canonical cysteine residue confers structural and kinetic stability. Ambiguous zinc coordination might be favorable for the evolution of zinc fingers.